Library Websites as Source of Marketing of Library Resources: An Empirical Study of HEC Recognized Universities of Pakistan - Abbas, Shahzad; Khalid, Shanawar; Hashmi, Fakhar Abbas (Qualitative and Quantitative Methods in Libraries, 2017)
The purpose of this paper is to analyze the current status of the university libraries in Pakistan. It is focused particularly on HEC recognized public and private sector universities. This paper will describe that at what extent libraries of the universities are relying on the website for communication with the student and for marketing purpose. For analysis in this study university library websites are extensively reviewed to gather the required information in accordance with the described feature. Total of 148 universities sites are reviewed which were further divided on the basis of direct and indirect link of the web sites.  Libraries websites were examined by the authors to gather the information regarding there use as a tool of marketing towards the students. This study identified that universities library websites are not fully developed in terms of using them as a marketing tool. This study also reveals that these website have lack of information and also don’t have collaborative interface with the users so that they can directly communicate with the end users and get the feedback for further enhancement in the technological development of the library. Finding of this study is limited to the universities that were recognized with the Higher Education Commission of Pakistan. It is difficult to generalize the result in other regions. This paper will be a step forward for the libraries to use the website as a marketing tool so that the libraries enhance their image by increasing their promotion and advertisement. This study will be helpful for the libraries in Pakistan. Common libraries also use this research finding to increase their users.